2021
DOI: 10.1515/psr-2021-0052
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric membranes for biomedical applications

Abstract: The rapid development of nanotechnology paved the way for further expansion of polymer chemistry and the fabrication of advanced polymeric membranes. Such modifications allowed enhancing or adding some unique properties, including mechanical strength, excellent biocompatibility, easily controlled degradability, and biological activity. This chapter discusses various applications of polymeric membranes in three significant areas of biomedicine, including tissue engineering, drug delivery systems, and diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 160 publications
0
3
0
Order By: Relevance
“…In response to question RQ1, in tissue engineering, the main properties exploited by the carotenoid are related to its antioxidant power, biocompatibility, antimicrobial activity and its ease of use in the composition of other products such as gels and polymeric membranes (Trombino et al, 2023;Woźniak-Budych, 2021). The studies identified investigated norbixin's properties in protective and healing coatings for wounds and in tissue repair and bone regeneration, as asked for in RQ2.…”
Section: The Pharmacological Activity Of Norbixin In Tissue Engineeringmentioning
confidence: 99%
“…In response to question RQ1, in tissue engineering, the main properties exploited by the carotenoid are related to its antioxidant power, biocompatibility, antimicrobial activity and its ease of use in the composition of other products such as gels and polymeric membranes (Trombino et al, 2023;Woźniak-Budych, 2021). The studies identified investigated norbixin's properties in protective and healing coatings for wounds and in tissue repair and bone regeneration, as asked for in RQ2.…”
Section: The Pharmacological Activity Of Norbixin In Tissue Engineeringmentioning
confidence: 99%
“…Membranes are defined as porous films that act as a separating barrier between two adjacent phases, capable of allowing the transport of substances from one phase to another in a selective manner [ 14 , 15 ]. In general, membranes utilized in the biomedical field can be used in tissue engineering, with a role in purification and in obtaining implants and scaffolds, in obtaining controlled release systems of active substances and in diagnosis, in the form of sensors and various diagnostic tests [ 16 ]. Membranes are classified according to their nature into natural membranes and artificial membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of membranes has become increasingly established in the biomedical field, and particularly in tissue engineering, with the realization of biological purification systems, protective coatings for wounds that accelerate healing, systems for diagnosis and therapy through the controlled release of active substances [ 10 ], and scaffolds. Scaffolds are the main resource of tissue engineering, which is concerned with restoring the functionality of damaged tissues and organs.…”
Section: Introductionmentioning
confidence: 99%